Determinación de Queratoconjuntivitis Seca en perros domésticos en la ciudadela Patricia Alarcón, del cantón Echeandía. - Herrera Gavilanez, Oliver Rodrigo (2025)
Keratoconjunctivitis Sicca (KCS) is an ophthalmological pathology that affects tear production and can cause symptoms such as eye irritation, dense secretion, frequent blinking, corneal pigmentation and, in advanced cases, blindness. Early diagnosis is key to avoiding serious complications, since without timely treatment, the disease can progress to total loss of vision. This study aimed to determine the presence of keratoconjunctivitis sicca (KCS) in domestic dogs from the Patricia Alarcón citadel, in the Echeandía canton, province of Bolívar, Ecuador. An evaluative and descriptive research was carried out, using the Schirmer test to measure tear production in 40 dogs of different breeds and ages. The Chi-Square statistical method was applied to analyze the data obtained. The results indicated that 75% of the dogs evaluated had normal tear production values, while 25% were classified as suspected of KCS, without any positive case being confirmed. In the analysis by age, it was observed that dogs older than 7 years showed a greater tendency to suspect the disease. However, no differences were found. Although this study found no confirmed positive cases, the presence of suspected cases suggests the need to monitor the patient's ocular health. Owners are recommended to attend regular veterinary check-ups and encourage the use of the Schirmer test in veterinary clinics. Furthermore, it is essential to promote education about this disease to improve its early detection.